ADMINISTRATIVE - LEGAL PROCEEDINGS OF COUNTERVAULT CORRUPTION IN THE FIELD OF CIVIL AVIATION - Гусар, Ольга Анатоліївна; Ущапівська, Анастасія Русланівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article defines and analyzes the norms of the Ukrainian legislation on corruption issues, investigates the legal aspects of the measures applied in the State Aviation Service in the activities of civil aviation actors and aims at minimizing the corruption manifestations in the field of civil aviation. Methods: of research in the work used dialectic method of cognition, general science and special methods. Results: the system of anti-corruption measures implemented by the authorized body in the field of civil aviation is determined. The proposed classification of anti-corruption measures in the field of civil aviation is divided into: legal, organizational and managerial; interaction with law enforcement agencies, public relations; personnel, logistical and financial support; international cooperation. The lack of coordination of anti-corruption communications and the need to use benchmarks for development and the results of state statistical observations and corruption experience, indexes of international ratings that assess the current situation in the field of prevention and counteraction to corruption in the field of civil aviation have been identified. Discussion: proposed ways to increase the effectiveness of the implementation of anti-corruption programs in the field of civil aviation and outlined the expected results of the implementation of anti-corruption measures in the field of civil aviation.